Judicial review of prosecutorial discretion in the initiation of investigations into situations of ‘sufficient gravity’ - Urs, P (Oxford University Press, 2020)

(untitled)
In the admissibility framework of the Rome Statute, the Prosecutor’s discretion as to whether to initiate an investigation into a situation includes the application of the open-textured requirement of ‘sufficient gravity’ specified in Article 17(1)(d). Pre-Trial Chamber oversight is designed to discipline the exercise of this discretion, but, in the absence of statutory guidance, the Pre-Trial Chambers are left themselves to articulate the standards of review of the Prosecutor’s admissibility assessments under relevant provisions, namely Articles 53(3)(a) and 15(4) of the Statute. The confused body of Pre-Trial Chamber practice to date poses the question as to what ought to be the standard of review of the Prosecutor’s admissibility assessment under each provision. This article teases apart and scrutinizes the standards of review that the Pre-Trial Chambers have applied in practice. By disaggregating the procedural contexts in which the Prosecutor’s admissibility assessments are made and analysing in each context the underlying interests at stake, it seeks to arrive at the appropriate standard of judicial review of the Prosecutor’s gravity assessment under each provision.